Comparativo de variedaes de Lactuca sativa L. en el comportamiento en hidroponía, Loreto - Soria Malaverry, Junior Orlando (2022)
Lettuce is one of the most consumed olive species in the diet, its cultivation is generally carried out in a conventional system, protection horticulture such as hydroponics allows to improve its vegetative adaptation and yield; the main objective was to determine the effect of sunlight intensity on the 3 types of varieties of Lactuca sativa. The nursery was made on a moistened sheet of paper towel, then after 5 days each seedling was placed in a sponge cube accommodated in a Styrofoam float fed in a source of nutrient solution, after 10 days they were transplanted to the 3” PVC tubes distributed at 1.0 m above the ground, each tube was fed with a circular flow sheet of nutrients, until harvest at 35 days. To evaluate the behavior and characteristics of the 3 lettuce varieties, there is a significant effect (p<0.01) between varieties for height, plant width, stem diameter, root length, number of leaves and root weight. In relation to the development of lettuce varieties grown in the NFT hydroponic technique under tropical climatic conditions, comparing the growth and development of agronomic characteristics and yield in order to improve horticultural technologies for protection against climate change in Loreto, it was evidence that the varieties show significant statistical significance in the vegetative behavior, being in this experiment the Tropicana variety with the highest plant weight (100.63 g).